2005
DOI: 10.1369/jhc.4b6437.2005
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Complex Chromosomal Rearrangement between Five Chromosomes in a Healthy Female Diagnosed in Preparation for Intracytoplasmatic Sperm Injection

Abstract: S U M M A R YWe report a case of a de novo complex chromosomal rearrangement among five chromosomes found in a clinically healthy woman. The only indication for chromosome analysis was a planned intracytoplasmatic sperm injection. Physical examination, including internal and external genitals, and ovaries and hormone status were normal. Banding cytogenetics showed a rearrangement among chromosomes #3, #4, #7, #9, and #17. Twenty-fourcolor fluorescence in situ hybridization and multicolor banding were applied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…Since DSB-containing chromosome domains have only limited mobility, chromosome domains in each other's vicinity would be more often involved, and chromosome domains located far apart in the gamete interphase nucleus are less likely to be involved in the same CCR. So in general more breakpoints than chromosomes should be involved in CCRs, an expectation that seems to be confi rmed by this report and other recent high-resolution analysed CCRs (Houge et al, 2003;Weise et al, 2003;de Vries et al, 2005;Gribble et al, 2005;Kuechler et al, 2005;Rosenberg et al, 2005). A single 'catastrophic' event causing multiple chromatin breaks could thus explain the origin of CCRs and other non-recurrent chromosomal aberrations (NRCAs).…”
Section: Discussionsupporting
confidence: 78%
“…Since DSB-containing chromosome domains have only limited mobility, chromosome domains in each other's vicinity would be more often involved, and chromosome domains located far apart in the gamete interphase nucleus are less likely to be involved in the same CCR. So in general more breakpoints than chromosomes should be involved in CCRs, an expectation that seems to be confi rmed by this report and other recent high-resolution analysed CCRs (Houge et al, 2003;Weise et al, 2003;de Vries et al, 2005;Gribble et al, 2005;Kuechler et al, 2005;Rosenberg et al, 2005). A single 'catastrophic' event causing multiple chromatin breaks could thus explain the origin of CCRs and other non-recurrent chromosomal aberrations (NRCAs).…”
Section: Discussionsupporting
confidence: 78%
“…However, similar to the aforementioned and discussed discordance of GTG-banding and molecular cytogenetic results confronted within this study there are few comparable cases available in the literature. What can be deduced from the literature is, that complex chromosomal rearrangements as in cases 10 and 30 are relatively rare events in infertility cases and can involve up to 5 or more different chromosomes (16)(17). The most complex rearrangement observed in this study was case 30 involving chromosome X, Y and 11.…”
Section: Types Of Rearrangements Observedmentioning
confidence: 47%
“…These authors divided CCRs in 2 broad groups: one group ≤ 4 breaks and the other group >4 breaks. They observed that most familial CCRs belonged to the group with up to 4 breaks and have been transmitted by a balanced female carrier, whereas most of the de novo CCRs belonged to the group with more than 4 breaks and were of paternal origin [Kousseff et al, 1993;Batista et al, 1994;Joyce et al, 1999;Lee et al, 2002;Grasshoff et al, 2003;Kuechler et al, 2005]. The majority of the reported cases had 4 or less breaks [Pellestor et al, 2011].…”
Section: Definition and Classification Of Ccrsmentioning
confidence: 99%